2019
DOI: 10.1186/s12984-019-0524-x
|View full text |Cite
|
Sign up to set email alerts
|

Visual attention, EEG alpha power and T7-Fz connectivity are implicated in prosthetic hand control and can be optimized through gaze training

Abstract: Background: Prosthetic hands impose a high cognitive burden on the user that often results in fatigue, frustration and prosthesis rejection. However, efforts to directly measure this burden are sparse and little is known about the mechanisms behind it. There is also a lack of evidence-based training interventions designed to improve prosthesis hand control and reduce the mental effort required to use them. In two experiments, we provide the first direct evaluation of this cognitive burden using measurements of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 63 publications
4
55
1
Order By: Relevance
“…This increased visual attention is most likely to compensate for the lack of tactile and proprioceptive feedback from their prostheses. A similar finding was also reported when able-bodied subjects were engaged in similar tasks using a prosthetic simulator (Blank et al, 2010; Sobuh et al, 2014; Parr et al, 2018, 2019). Almost all of these studies investigated this disruption in eye-hand coordination precisely for this reason, namely to measure the subject's proficiency in controlling the prosthesis.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…This increased visual attention is most likely to compensate for the lack of tactile and proprioceptive feedback from their prostheses. A similar finding was also reported when able-bodied subjects were engaged in similar tasks using a prosthetic simulator (Blank et al, 2010; Sobuh et al, 2014; Parr et al, 2018, 2019). Almost all of these studies investigated this disruption in eye-hand coordination precisely for this reason, namely to measure the subject's proficiency in controlling the prosthesis.…”
Section: Introductionsupporting
confidence: 82%
“…Although Figure 4B suggests that this window will at least be as long for amputated users, one may argue that this result is not representative for movements performed with a prosthesis. However, previous studies showed without exception that prosthetic users still fixate the target object for the majority of the reaching phase (Bouwsema et al, 2012; Sobuh et al, 2014; Chadwell et al, 2016; Hebert et al, 2019; Parr et al, 2019), albeit alternating it more often with fixations on the hand (i.e., the “switching” strategy). Moreover, this reaching phase may actually take more than twice as long as compared to the same movement performed with the anatomical limb (Sobuh et al, 2014; Hebert et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…A target-locking score was then calculated by subtracting the percentage of cursor fixation time from the percentage of target fixation time to create a ratio measure of the allocation of visual attention. This method has previously been used to determine the gaze control of participants performing visuomotor adaptation tasks (Marshall et al, 2019), surgical tasks (Wilson, McGrath, Vine, Brewer, Defriend & Masters , 2010), and tasks involving the control of a prosthetic hand (Parr, Vine, Harrison & Wood, 2018;Parr, Vine, Wilson, Harrison & Wood, 2019). Using this method, a more positive score reflects more time fixating on targets whereas a negative score reflects more time spent fixating the cursor.…”
Section: Target-locking Scorementioning
confidence: 99%
“…A score of '0' reflects equal time spent fixating the cursor and targets and represents a 'switching strategy'. This has been shown to be a reliable measure of eye-hand coordination in studies (1) examining expertise in prosthetic hand control (Parr et al, 2018) and surgery (Wilson et al, 2010); (2) in studies that have examined the development of eye-hand coordination (Parr, Vine, Wilson, Harrison & Wood, 2019;Wilson et al, 2011); and (3) in studies examining the effect of pressurized performance environments on eye-hand coordination (Vine, Freeman, Moore, Chandra-Ramanan, & Wilson, 2013).…”
Section: Gaze Controlmentioning
confidence: 99%